ASSA13-10-10 CREG Promotes Vasculogenesis of Embryonic Stem Cells by Activating PI3K/Akt/VEGF Pathway. (29th April 2013) - Xiaoxiang, Tian; Na, Zhang; Jian, Kang; Jian, Zhang; Chengfei, Peng; Chenghui, Yan; Yaling, Han
Abstract : Background: Vasculogenesis plays an important role under both physiological and pathological conditions. Factors controlling vasculogenesis is still far to be fully elucidated. Cellular repressor of E1A activating gene (CREG) has been reported to be highly expressed in endothelium and prevent injured endothelial cells from apoptosis, suggesting its potential role in regulating vasculogenesis. Objective: The aim of this study was to investigate the role and mechanism of CREG in regulating vasculogenesis of embryonic (ES) stem cells. Methods: CREG over-expression ( wt CREG) and knock-down ( sh CREG) ES cell lines were established by transfection of wild type ES cell R1 (wtR1) with pCXN2-Flag-CREG-IRES-EGFP and mouse CREG shRNA vectors respectively, using ES cells expressing EGFP as a control (ctlR1). We first detected CREG expression during wtR1 and ctlR1 differentiation by Western Blot. Then embryoid bodies (EB) derived from 4 groups of ES cells were plated on fibronectin coated cover slips and cultured for 10 days to make an in vitro vasculogenesis model. Endothelial network formation was detected by CD31 immunofluorescence. Transcription of CD31, VEGFR2 and VEGF were measured by real time polymerase chain reaction (RT-PCR). Protein involved in several signalling pathways, including JNK, ERK1/2, PI3K/Akt and VEGFR2, VEGF were detected by Western Blot. PI3K/Akt inhibitor and VEGF neutralising antibody were used for blocking study in wt CREG group. VEGF were supplemented for rescue study in sh CREG group. Results: Expression of CREG increased with differentiation of ES cells in control group (wtR1 and ctlR1). wt CREG had significantly higher density of endothelial network formation identified by CD31 immunofluorescence in contrast to sh CREG, which barely had endothelial network formation. RT-PCR also showed that transcription level of CD31, VEGFR2 and VEGF are up-regulated in wt CREG and down-regulated in sh CREG. Western blot showed no difference in JNK, ERK1/2, but significant change of PI3K/Akt, VEGFR2, VEGF parallel to CREG expression in 4 groups. Blocking assay showed that PI3K/Akt inhibitor wortmannin and VEGF neutralising antibody could effectively eliminate the CREG induced vasculogenesis, and VEGF could successfully rescue failed vasculogenesis due to CREG gene silence. Conclusions: CREG promotes vasculogenesis of ES cells by activating PI3K/Akt/VEGF pathway.